Lost in Aggregation: The Geographic Distribution of Kwashiorkor in Eastern Democratic Republic of the Congo. Issue 4 (December 2018) - Fitzpatrick, Merry; Ghosh, Shibani; Kurpad, Anura; Duggan, Christopher; Maxwell, Daniel
Background: Kwashiorkor is a major classification of severe acute malnutrition whose etiology remains elusive. It is estimated to affect hundreds of thousands of children annually, but no accurate global prevalence figures are available. Little is known how prevalence varies within populations, an important undocumented aspect of kwashiorkor obscured by the aggregation of prevalence or incidence of the condition across large populations and geographic areas. Objective: To estimate the prevalence of kwashiorkor in select neighboring villages of the eastern Democratic Republic of the Congo (DRC) and assess if prevalence can vary dramatically among neighboring villages. Methods: An anthropometric census survey evaluated 1328 children aged 12 to 59 months within all 19 villages in one health area of eastern DRC, recording all cases of kwashiorkor, diagnosed by bipedal pitting edema. Results: Village-level prevalence of kwashiorkor in the study area varied from 0% to 14.9%. Interviews with health services staff in the study area and across 2 provinces confirmed that current differences in prevalence reflect a long-term pattern and are a common feature of kwashiorkor throughout this region. Conclusions: Aggregation of kwashiorkor prevalence and incidence data across large populations or geographic regions poses several risks to understanding the epidemiology of kwashiorkor. If clustering of kwashiorkor is not taken into account, (1) nutritional crises in particular villages may go undetected; (2) the real effect of interventions may be underestimated; (3) interventions may be inappropriately targeted, leading to reduced coverage, efficacy, and cost-efficiency; and (4) important insights into the root causes of kwashiorkor may be lost.